Improving Science Learning for Grade IV Using Virtual Reality Media on Student Learning Outcomes at SD Inpres 1 Tanamodindi - Nur Aini; Juraid Abdul Latief; Rizal Rizal; Zulnuraini Zulnuraini; Kasmawati Kasmawati (Papanda Publisher, 2026)
Reading literacy is a foundational competency that underpins academic achievement and broader social participation, yet Indonesian elementary students continue to perform below international benchmarks, with low reading interest compounding deficits in learning comprehension. This qualitative descriptive study examined the implementation of a reading literacy programme and its associations with learning interest and comprehension among 28 fifth-grade students at SD Negeri 8 Palu during the 2024/2025 academic year. Data were collected through structured observation, semi-structured interviews, validated questionnaires, and documentation, and analysed using Miles and Huberman's interactive model. Results indicated that the programme was implemented consistently through daily fifteen-minute pre-class reading routines, classroom reading corner utilisation, and teacher-facilitated retelling activities. Students demonstrated high learning interest (M = 30.2/32; 94.4%) and high learning comprehension (M = 28.5/32; 89.1%) across all measured indicators. Notably, an affective–cognitive gap was observed: learning interest scores outpaced comprehension scores, with main idea identification emerging as the weakest comprehension sub-skill. These findings suggest that habituation-based literacy programmes effectively build motivational engagement but require integration of explicit comprehension strategy instruction to generate proportional cognitive gains. The study contributes contextual evidence from Central Sulawesi and advances a theoretically significant argument for coupling reading routines with targeted strategy scaffolding in Indonesian elementary literacy education.